2002
DOI: 10.1046/j.1523-1755.2002.00201.x
|View full text |Cite
|
Sign up to set email alerts
|

Management of hemodialysis catheter-related bacteremia with an adjunctive antibiotic lock solution

Abstract: Use of an antibiotic lock, in conjunction with systemic antibiotic therapy, can eradicate catheter-associated bacteremia while salvaging the catheter in about one half of cases. Moreover, this management approach offers clinical advantages over routine catheter exchange.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
175
1
6

Year Published

2002
2002
2022
2022

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 256 publications
(194 citation statements)
references
References 24 publications
8
175
1
6
Order By: Relevance
“…However, probable catheter-related bacteremia was diagnosed in only 60% of cases with suspected infection, emphasizing the importance of considering other sources of infections in catheter-dependent patients. This finding is in agreement with three prior studies that reported a 59% to 81% likelihood of bacteremia in catheterdependent patients with suspected infection (12)(13)(14). The other infections included secondary-access (fistula, graft, or peritoneal dialysis catheter) infection and nonaccessrelated infection.…”
Section: Discussionsupporting
confidence: 92%
“…However, probable catheter-related bacteremia was diagnosed in only 60% of cases with suspected infection, emphasizing the importance of considering other sources of infections in catheter-dependent patients. This finding is in agreement with three prior studies that reported a 59% to 81% likelihood of bacteremia in catheterdependent patients with suspected infection (12)(13)(14). The other infections included secondary-access (fistula, graft, or peritoneal dialysis catheter) infection and nonaccessrelated infection.…”
Section: Discussionsupporting
confidence: 92%
“…None of the patients of these study required catheter removal to cure the CRB [39]. In two subsequent studies, with a vancomycin-gentamicin-heparin lock, 35% and 38% of patients, respectively, failed AML therapy and required catheter exchange [40,41]. In a more recent prospective study, similar results were reported when gentamicin was replaced at the AML solutions with ceftazidime because of reported episodes of gentamicininduced ototoxicity.…”
Section: Time For Preventing Recurrence Of Catheter-related Bacteremiamentioning
confidence: 74%
“…Empiric antibiotics were initiated after blood cultures were obtained. Patients received a 3-week course of systemic antibiotics, in conjunction with an antibiotic-heparin lock instilled into the catheter lumen (12,13). The dialysis catheter was replaced in patients with persistent symptoms despite appropriate antibiotics or in patients with recurrent bacteremia.…”
Section: Management Of Catheter Malfunction and Infectionmentioning
confidence: 99%